Truly Electroforming‐Free and Low‐Energy Memristors with Preconditioned Conductive Tunneling Paths. (3rd August 2017) - Yoon, Jung Ho; Zhang, Jiaming; Ren, Xiaochen; Wang, Zhongrui; Wu, Huaqiang; Li, Zhiyong; Barnell, Mark; Wu, Qing; Lauhon, Lincoln J.; Xia, Qiangfei; Yang, J. Joshua
Abstract : 1S1R (1 selector and 1 memristor) is a laterally scalable and vertically stackable scheme that can lead to the ultimate memristor density for either memory or neural network applications. In such a scheme, the memristor device needs to be truly electroforming‐free and operated at both low currents and low voltages in order to be compatible with a two‐terminal selector. In this work, a new type of memristor with a preconditioned tunneling conductive path is developed to achieve the required performance characteristics, including truly electroforming‐free, low current below 30 µA (potentially <1 µA), and simultaneously low voltage ≈±0.7 V in switching operations. Such memristors are further integrated with two types of recently developed selectors to demonstrate the feasibility of 1S1R integration. Abstract : This study proposes and experimentally demonstrates a truly electroforming‐free device with both low switching current and voltage for the first time. The exemplary device with a Ta/Ta2 O5 :Ag/Ru‐stack structure functions based on conductive tunneling paths. The low operation current and voltage make the memristors highly compatible with two‐terminal selectors. 1S1R integrate cells are demonstrated with both ionic selector and electronic selector.